Concentration of Heavy Metal Pb and Cu in Reef Fish at the Waters of Miang Besar Island in Kutai Timur Regency - Pajar, Zulkifli; Rafii, Akhmad; Ghitarina, Ghitarina (Nusantara Tropical Fisheries Science (Ilmu Perikanan Tropis Nusantara), 2023)
Miang Island is a transportation route for coal ships and a place for loading and unloading coal, then there are also oil palm companies around this island. On this island there are also still islanders who carry out household activities in this area, such as washing activities, thus producing household waste in the waters on this island. Therefore, community activities carried out on this island can contribute to the burden of pollution of waters and reef fish in these waters, therefore it is necessary to conduct research on heavy metal levels that have contaminated organisms in these waters related to the pollution conditions that occur. This research was conducted in February 2023 in the waters of miang island and analyzed water quality and heavy metal content in the water quality laboratory and soil laboratory of mulawarman university. The parameters that will be observed are the analysis of heavy metals lead (Pb) and copper (Cu) found in reef fish meat and statistical analysis using the Chi-Square test by comparing heavy metal content in reef fish against water quality data. In this study, reef fishes that have been analyzed are Lutjanus decassatus, Pentapodus caninus, Ephnephlesu ongus, Lethrinus erythropetrus, Balistapus undulatus, Gymnocranius microdon, Plectropomus leopardus, and Priacanthus meeki. All fish species contain heavy metals lead (Pb) and copper (Cu), this can be caused by activities carried out by local communities that can disturb water conditions and have an impact on fish, In the Chi-square analysis that has been carried out on water quality at each station on Miang Island, the results obtained water quality gives an influence on heavy metals in the bodies of reef fish that have been caught in this study. This can be caused by water quality that is affected by heavy lead (Pb) and copper (Cu) from human activities in these waters, such as ship loading and unloading activities, and ship transportation routes.